Sources, Composition, and Export of Particulate Organic Matter Across British Estuaries. Issue 4 (12th April 2023) - García‐Martín, E. Elena; Sanders, Richard; Evans, Chris D.; Kitidis, Vassilis; Lapworth, Dan J.; Spears, Bryan M.; Tye, Andy; Williamson, Jennifer L.; Balfour, Chris; Best, Mike; Bowes, Michael; Breimann, Sarah; et al.
Abstract: Estuaries receive and process a large amount of particulate organic carbon (POC) prior to its export into coastal waters. Studying the origin of this POC is key to understanding the fate of POC and the role of estuaries in the global carbon cycle. Here, we evaluated the concentrations of POC, as well as particulate organic nitrogen (PON), and used stable carbon and nitrogen isotopes to assess their sources across 13 contrasting British estuaries during five different sampling campaigns over 1 year. We found a high variability in POC and PON concentrations across the salinity gradient, reflecting inputs, and losses of organic material within the estuaries. Catchment land cover appeared to influence the contribution of POC to the total organic carbon flux from the estuary to coastal waters, with POC contributions >36% in estuaries draining catchments with a high percentage of urban/suburban land, and <11% in estuaries draining catchments with a high peatland cover. There was no seasonal pattern in the isotopic composition of POC and PON, suggesting similar sources for each estuary over time. Carbon isotopic ratios were depleted (−26.7 ± 0.42‰, average ± sd) at the lowest salinity waters, indicating mainly terrigenous POC (TPOC). Applying a two‐source mixing model, we observed high variability in the contribution of TPOC at the highest salinity waters between estuaries, with a median value of 57%. Our results indicate a large transport of terrigenous organic carbon into coastal waters, where it may be buried, remineralized, or transported offshore. Plain Language Summary: Estuaries transport and process a large amount terrigenous particulate organic matter (i.e., carbon and nitrogen) prior to its export to coastal waters. In order to understand the fate of organic carbon and the role of estuaries in the global carbon cycle it is essential to improve our knowledge on its composition, origin, and amount of carbon transported. We quantified the elemental concentrations and stable isotopes composition of carbon and nitrogen to quantify the amount of terrigenous particulate organic matter transported by 13 British estuaries, which drain catchments of diverse land cover under different hydrological conditions. We found a great variability in particulate organic carbon (POC) and particulate organic nitrogen concentrations across the salinity gradient, implying inputs, and losses of material within the estuaries. Each estuary had similar sources of particulate material throughout the year. In most of the estuaries, the POC had a terrigenous origin at the lowest salinity waters. The terrigenous organic carbon contribution decreased toward coastal waters with an average contribution of 57% at the highest salinity waters, indicating a large transport of terrigenous organic carbon into coastal waters. Key Points: High interestuarine spatial and intraestuarine temporal particulate organic carbon (POC) variability Similar sources of particulate material throughout the year within each estuary Estimated average contribution of terrigenous POC from estuaries to coastal waters was 57%